ANTIDIABETIC EFFECTS OF RICINUS COMMUNIS ON THE BLOOD BIOCHEMICAL PARAMETERS IN STREPTOZOTOCIN INDUCED ALBINO RAT - SEEMA MANN; P. K. SINGH; ANITA; ANIL KUMAR GUPTA (International Journal of Pharma and Bio Sciences, 2013)
The present investigation was carried out to evaluate the antidiabetic effects of Ricinus communis leaves extract on the streptozotocin induced diabetic rats. Oral administration to ethanolic leaves extract was given (200mg/kg body weight) for 7, 15, 30, 45 and 60 days respectively. The decreased cholesterol, HDL, LDL, triglyceride and insulin; while increased SGOT, SGPT, ALP, ACP and glucose after streptozotocin induction, however, increased and decreased significantly after Ricinus communis treatment respectively. The results clearly show that the extract of Ricinus communis potent hypoglycemic activity.